Grain sorghum response to postemergence applications of mesotrione and quizalofop - Abit, Mary Joy Manacpo (Kansas State University, 2010)
Growth chamber, greenhouse and field experiments using conventional grain sorghum were conducted to 1) evaluate the differential response of grain sorghum hybrids to POST application of mesotrione at various rates and application timings, and 2) determine the physiology of tolerance of grain sorghum hybrids to mesotrione. Sorghum response ranged from susceptible to tolerant. Mesotrione dose-response studies on four sorghum hybrids revealed that injury symptoms were greatest in Pioneer 85G01 and least in Asgrow Seneca. Mesotrione applied EPOST (early POST) injured sorghum more than when applied at MPOST (mid POST) or LPOST (late POST) timings. Observed injury symptoms were not well correlated with grain yield and were transient, thus injury did not reduce sorghum grain yield. Foliar absorption or translocation of mesotrione in tolerant hybrids did not differ with that of susceptible hybrids but metabolism was more rapid in tolerant than in susceptible hybrids. Initial grain sorghum injury was severe and will likely be a major concern to producers. Field and growth chambers studies were conducted on herbicide-resistant grain sorghum to 1) determine the effect of quizalofop rates, application timings, and herbicide tank mixes on acetyl-coenzyme A carboxylase (ACCase)-resistant grain sorghum injury and yield, and 2) determine if herbicide metabolism is an additional mechanism that could explain the resistance of ACCase- and acetolactate synthase (ALS)-resistant grain sorghum. Depending on rate, EPOST application caused the greatest injury while the least injury occurred with LPOST application. Crop injury from quizalofop was more prominent at rates higher than the proposed use rate (62 g ha [superscript]-1) in grain sorghum. Sorghum grain yield was not affected by quizalofop regardless of rates or application timings. Weed control was greater when quizalofop was applied with other herbicides than when applied alone. Herbicide treatments except those that included 2,4-D caused slight to no sorghum injury. Results of the quizalofop metabolism study do not support the involvement of differential metabolism in the observed response of grain sorghum to quizalofop. Rimsulfuron metabolism by ALS-resistant sorghum is more rapid than the susceptible genotypes, thus explaining the observed rapid recovery of grain sorghum plants from rimsulfuron injury in the field.
Keywords: mesotrione; quizalofop; herbicide resistant grain sorghum; grain sorghum response; postemergence application; Agriculture, Agronomy (0285)